(untitled) (CIPEEX, 2025)
This study analyzes the intersection between property rights and environmental protection in Brazil, focusing on the impact of illegal burning practices. The Federal Constitution of 1988 establishes that property must fulfill a social function and respect the environment. In the penal sphere, illegal burning is considered an environmental crime, subjecting offenders to penalties. The analysis incorporates Karl Marx’s perspective, which criticizes private property as a source of inequality and environmental degradation, and Émile Durkheim’s view on the need for social norms that promote solidarity and sustainable practices. The text discusses challenges such as deforestation, social inequality, lack of environmental education, and inadequate infrastructure. Real cases are presented to illustrate the environmental responsibility of companies and individuals, highlighting the importance of legislation such as the Environmental Crimes Law. Finally, it suggests that promoting sustainable practices and raising awareness about conservation are essential to balance property rights with environmental protection.